Thyroid hormone therapy and procurement of livers from brain-dead donors. (2nd July 2016) - Novitzky, Dimitri; Mi, Zhibao; Videla, Luis A.; Collins, Joseph F.; Cooper, David K. C.
ABSTRACT: Hormonal therapy to brain-dead potential organ donors remains controversial. A retrospective study was carried out of hormonal therapy on procurement of organs in 63, 593 donors in whom information on T3 /T4 therapy was available. In 40, 124 donors, T3 /T4 and all other hormonal therapy was recorded. The percentages of all organs procured, except livers, were greater in T3 /T4 -treated donors. Nevertheless, if T3 /T4 therapy had been administered to the donor, liver transplantation was associated with significantly increased graft and recipient survival at 1 month and 12 months. The potential reasons for the lack of effect of T3 /T4 therapy on the number of livers procured are discussed.